Effectiveness of using pen tablets in the form of youtube based videos in basic analytical chemistry courses in the digital era after the pandemic - Febri Yanti; Anita Debora Simangunsong (Institute of Computer Science (IOCS), 2023)
The problem with tablet pens is only done during online learning. For this reason, pen tablets can be used in offline/face-to-face learning with the help of a projector. Not only that, this research also uses the YouTube application to upload recorded classroom learning so that it can be accessed by many people, especially students taking basic analytical chemistry classes. The aim of this research is to determine the effectiveness of using pen tablets in learning basic analytical chemistry courses in the digital era after the pandemic with offline/face-to-face learning and using the YouTube application to help students repeat basic analytical chemistry lessons so as to improve student learning outcomes. The research method in this study is descriptive qualitative and quantitative methods. Student interest according to the questionnaire has an average score of 3.78 in the good category and there is an increase in learning outcomes so that the effectiveness is 79%.